Developing Arabic writing skills: peer feedback in online forum facility on moodle - Abd Hamid, Mohd Azrul Azlen; Mat Daud, Nuraihan; Mat Daud, Nor Shidrah (IDOSI Publications, 2014)
The use of a learning management system (LMS) has brought a renewed attention to language teaching. Yet, a question that remains to be answered is the extent to which the system can be used to support the pedagogical approach adopted by the instructor. This paper discusses the use of Moodle as a platform for teaching Arabic in a task-based teaching environment. The LMS was used to develop students’ Arabic writing skills. Over the course of one semester, 15 pre-university students in an FL Arabic course submitted their term paper via the LMS and discussed their work using the same platform. The comparison was also made between the products of the two tasks. The study found that the quality of writing improved and there was a positive correlation between the number of words used in discussing the topic and the quality of writing produced.